Effects of Immunomodulatory Nutritional Therapy in cancer patients who have undergone gastrointestinal surgery: a scoping review (Research, Society and Development, 2022)
Introduction: Malnutrition represents a determining factor in the clinical outcome of surgical patients, since it can negatively influence the postoperative period, favoring the onset of complications such as delayed wound healing, infections, increased hospital stay, and consequently, mortality. Gastrointestinal tract surgeries in oncologic patients present high rates of complications and morbidity and mortality. Immunomodulatory nutritional therapy has been frequently used in these patients for its high potential to modulate immune activity, often contributing to the improvement of immune function and, consequently, favoring the clinical evolution. Method: This is a scoping review that will take place from September 2021 to January 2022. Studies in English and Portuguese were reviewed, and the databases selected for the search were Latin American and Caribbean Health Sciences Literature (LILACS), MEDLINE/PUBMED, plus gray literature. Results: Thirty-eight potentially eligible publications were identified, and the final sample consisted of 11 studies that evaluated the clinical outcome of cancer patients who received immunomodulatory nutritional therapy in the perioperative period of gastrointestinal surgery. Conclusion: The studies have shown that offering immunomodulatory formulas orally or enterally to cancer patients who have undergone gastrointestinal surgery has brought benefits, reducing complications such as infections and length of stay and providing better results in albumin level as well as in relation to immune function, raising the quality of life of patients. Some points such as mortality and T-lymphocyte increase could not be proven, suggesting that further studies should be conducted.